2021
DOI: 10.3390/ph14040320
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept Ameliorates Cardiac Fibrosis in Rats with Diet-Induced Obesity

Abstract: Diet-induced obesity (DIO) is considered the main risk factor for cardiovascular diseases. Increases in the plasma levels of tumor necrosis factor alpha (TNF-α) is associated with DIO. Etanercept, a TNF-α inhibitor, has been shown to alleviate cardiac hypertrophy. To investigate the effect of etanercept on cardiac fibrosis in DIO model, rats on high fat diet (HFD) were subdivided into two groups: the etanercept group and vehicle group. Cardiac injury was identified by classic methods, while fibrosis was charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 69 publications
4
6
0
Order By: Relevance
“…These findings were consistent with the reports of Hsu et al, who observed that ETA administration significantly reduced HFD-induced obesity 14 . The ability of ETA to inhibit any increase in body weight is attributed to its inhibition of TNF-α, the key inducer of adipogenesis and obesity 42 , 44 .…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…These findings were consistent with the reports of Hsu et al, who observed that ETA administration significantly reduced HFD-induced obesity 14 . The ability of ETA to inhibit any increase in body weight is attributed to its inhibition of TNF-α, the key inducer of adipogenesis and obesity 42 , 44 .…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported that TNF-α influences the adipose production of profibrogenic factors, such as leptin, and inhibits the expression and activity of adiponectin 47 , 48 . This resulted in significantly elevated adiponectin levels and normalized leptin levels in the ETA-treated group, which competitively prevented the binding of TNF-α to its receptor, causing its inhibition 14 . Consequently, ETA ameliorated adipocyte dysfunction and aids in the prevention of intrahepatic lipid accumulation and the enhancement of both insulin sensitivity 49 and endothelial functions that counteract hypertension, as detected in the present study 27 .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations